Non-deletional alpha thalassaemia: a review - Ibrahim Kalle Kwaifa; Mei I. Lai; Sabariah Md Noor (Orphanet Journal of Rare Diseases, 2020)
Abstract Background Defective synthesis of the α-globin chain due to mutations in the alpha-globin genes and/or its regulatory elements leads to alpha thalassaemia syndrome. Complete deletion of the 4 alpha-globin genes results in the most severe phenotype known as haemoglobin Bart’s, which leads to intrauterine death. The presence of one functional alpha gene is associated with haemoglobin H disease, characterised by non-transfusion-dependent thalassaemia phenotype, while silent and carrier traits are mostly asymptomatic. Main body Clinical manifestations of non-deletional in alpha thalassaemia are varied and have more severe phenotype compared to deletional forms of alpha thalassaemia. Literature for the molecular mechanisms of common non-deletional alpha thalassaemia including therapeutic measures that are necessarily needed for the understanding of these disorders is still in demand. This manuscript would contribute to the better knowledge of how defective production of the α-globin chains due to mutations on the alpha-globin genes and/or the regulatory elements leads to alpha thalassaemia syndrome. Conclusion Since many molecular markers are associated with the globin gene expression and switching over during the developmental stages, there is a need for increased awareness, new-born and prenatal screening program, especially for countries with high migration impact, and for improving the monitoring of patients with α-thalassaemia.